Principal Leadership and Teacher Performance at SMP TASTAFI Darussalamah Al-Aziziyah - Nasruddin (Wasatha: Jurnal Studi Islam dan Humaniora, 2025)
Teacher performance includes several important things. First, teachers must be able to teach the material effectively. In addition, good interaction with students is very important to build positive relationships and motivate them. Teachers need to plan and prepare lesson materials well, as well as assess student progress and provide feedback. Professional development, such as attending training, is an important part of teacher performance. This study aims to principals in improving teacher performance through principal leadership. This research approach is the result of field research with a qualitative descriptive research approach. Increasing the quality of education at SMP TASTAFI Darussalamah Al-Aziziyah, principals need to take the following strategic steps. First, improve teacher training and professional development by providing specific training and workshops on the latest teaching techniques. Second, increase financial support for teachers, such as additional allowances, performance-based incentives, and professional development funds. Third, adjust teacher placement to their educational background and conduct competency assessments periodically. In addition, create a positive work environment. Finally, principals must build partnerships with educational institutions or other organizations to obtain additional resources, as well as hold internship programs to broaden teachers’ experiences and perspectives.